Sōka Gakkai in Cuba - Rodriguez Plasencia, Girardo (Journal of Religion in Japan, 2014)
Sōka Gakkai began to develop in Cuba as a religious organization after the visit of Ikeda Daisaku in 1996. Starting with a small group in the capital city, it received juridical recognition by the State in 2007 and has spread to most of the provinces in the country. Despite its modest growth, the Cuban case provides insights into the ways in which this religion develops in new sociocultural environments and thereby participates in the dynamics of globalization beyond Japanese enclaves. Based on the analysis of data collected in Havana, the article identifies, describes and explains four modes by which Sōka Gakkai negotiates its message and identity in Cuba: the hybridization of Sōka Gakkai themes with the life and thought of National Hero José Martí; the universalization of Sōka Gakkai’s particularistic Japanese elements to create a new identity connected to the movement’s global following; the hybridization of Sōka Gakkai with ‘Oriental’ spiritualities; and the combination of pluralism, inclusivism and exclusivism as a threefold attitude toward other religions. These modes involve multiple interactions in the global field, through which Sōka Gakkai strives to build a symbolic bridge to local particularism, the ‘mystic East,’ and the world.